Development of Islamic Religious Education Curriculum Based on Research and Local Wisdom - Eti Sapitri; Sri Murhayati; Nurhasnawati (JEICI - Journal of Education and Islamic Contemporary Issue, 2026)
The curriculum is a central component of educational implementation, serving as a guide for the learning process. However, the existing Islamic Religious Education curriculum remains general and normative and has not yet fully addressed society's real needs and global challenges. This article proposes an alternative approach to developing an Islamic Religious Education curriculum, grounded in research and local wisdom, as a strategic effort to enhance its relevance, contextualization, and applicability to students' lives. This study employs a library research method by analyzing relevant literature, journals, and documents. The findings indicate that a research-based curriculum can present learning grounded in data, empirical evidence, and real-world problem-solving. Meanwhile, the integration of local wisdom, which constitutes an essential part of local community needs, enables the curriculum to be more attuned to the culture, potential, and challenges of the surrounding community, thereby allowing Islamic values to be internalized more effectively and meaningfully. An Islamic Religious Education curriculum grounded in research and local wisdom serves not only as a learning guide but also as an instrument for shaping a religiously critical, moderate, and broad-minded generation without compromising Islamic and national identity. Therefore, developing an Islamic Religious Education curriculum grounded in research and local wisdom is crucial to improving educational quality and strengthening community empowerment in the modern era.